2021
DOI: 10.1016/j.ijid.2020.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Synovial fluid presepsin as a novel biomarker for the rapid differential diagnosis of native joint septic arthritis from crystal arthritis

Abstract: To investigate whether presepsin can be used as a novel biomarker to differentiate between native joint septic arthritis (NJSA) and crystal arthritis (CA). Methods: This study included 75 patients diagnosed with either NJSA (n = 21) or CA (n = 54). Presepsin in synovial fluid and blood, C-reactive protein, and procalcitonin were measured and compared between the NJSA and CA groups. Receiver operating characteristic (ROC) curve analyses were performed to differentiate between the two groups. Results: Synovial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…In this study, intra‐operative findings and synovial fluid markers such as synovial WBC counts were not associated with the need for secondary surgery. Whilst there appears to be ample evidence advocating for the use of synovial white blood cell counts to diagnose septic arthritis [11, 13, 21], the role of synovial white blood cell counts to predict effectiveness of surgical debridement for septic arthritis is less established [29]. Stake et al [30] found that taken in isolation, the increased synovium WBC counts did not significantly predict patients who required secondary surgery for knee septic arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, intra‐operative findings and synovial fluid markers such as synovial WBC counts were not associated with the need for secondary surgery. Whilst there appears to be ample evidence advocating for the use of synovial white blood cell counts to diagnose septic arthritis [11, 13, 21], the role of synovial white blood cell counts to predict effectiveness of surgical debridement for septic arthritis is less established [29]. Stake et al [30] found that taken in isolation, the increased synovium WBC counts did not significantly predict patients who required secondary surgery for knee septic arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Presepsin has been attracting attention as a useful marker for diagnosis and prognosis in sepsis [6]. Since presepsin production is increased at the site of infection, its measurement in the joint uid is effective in differentiating pyogenic arthritis from crystalline arthritis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Presepsin has been attracting attention as a useful marker for diagnosis and prognosis in sepsis [ 6 ]. Since presepsin production is increased at the site of infection, its measurement in the joint fluid is effective in differentiating pyogenic arthritis from crystalline arthritis [ 7 ]. The cerebrospinal fluid presepsin is also useful for the diagnosis and prognosis of post-neurosurgical ventriculitis/meningitis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%